Exchange Rate Pass-Through in Brazil - Belaisch, Agnes (Washington, D.C. : International Monetary Fund, 2003)
In the last two years the real has undergone a large depreciation and the central bank has missed its inflation target in 2002 for the second year in a row. Inflation, however, has increased much less than the rate of currency depreciation and the pickup in inflation in the last quarter of 2002 raises the question of whether the exchange rate passthrough has finally risen. This paper argues that the passthrough in Brazil has fallen compared with estimates in other studies on earlier time periods, and remains low when compared with the passthrough in other Latin American countries. Indeed the passthrough is more comparable with that of G-7 countries-although in Brazil the effect on prices appears to be faster.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet